Studi Keanekaragaman Jenis Burung di Taman Wisata Alam Baumata, Kabupaten Kupang, Provinsi Nusa Tenggara Timur. - Salomo Y Banoet; Maria M. E. Purnama; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2020)
Indonesia is one of the countries with a high level of diversity, including in the bird category, there are 1,771 species found in Indonesia, of which there are 533 protected species. Baumata Nature Park is one of the nature conservation areas included in the Kupang Regency,Taebenu District. This study aims to determine the diversity of bird species in Baumata Nature Park, carried out for 2 months from October-November 2019 using the point transect method and the MacKinnon method. From the analysis using the MacKinnon method, it was found that there were 27 bird species from 17 tribes, of all bird species there were 20 species of birds endemic to Nusa Tenggara, namely Isap madu timor (Lichmera flavincans), Burung madu matari (Nectarinia solaris), Kancilan timor (Pachycephala orpheus), Anis timor (Zoothera peronii), Decu timor (Saxicola caprata), Cikrak timor (Phylloscopus presbtyes), Meliphaga dada lurik (Meliphaga reticulata), Bondol pancawarna (Lonchura quinticolor), Kacamata limau (Zosterops citrinellus), Pipit zebra (Taeniopygia guttata), Ayam hutan merah (Gallus gallus), Burung madu matari (Nectarinia solaris), Walet sapi (Collocalia esculenta), Burung gereja erasia (Passer montanus), Kipasan dada hitam (Rhipidura rufifrons), Srigunting walaceae (Dicrurus densus), Cikrak dada kuning (Seicercus montis), Puyuh coklat (Coturnix ypsilophora) Tekukur biasa (Streptopelia chinensis), Elang boneli (Hieraaetus fasciatus) and 1 type of migrant bird, namely Kirik-kirik australia (Merops ornatus). The most common types of birds in Baumata Nature Park are insectivorous and nectar species. The diversity of bird species in Baumata Nature Park has an H 'value of 3.15 with a high category.